Death in the Krasiński Family from a private perspective: the life of Eliza Krasińska, née Branicka under the shadow of death - Górczyk, Wojciech Jerzy (Marginesy, 2021)
Death is always a traumatic experience for those closest to the deceased. This was true for Eliza Krasińska, née Branicka, who lost her daughter, father‑in‑law and husband in a short space of time. An accompanying feature of death is a funeral. In the 19th C, the Krasiński family established atradition which consisted of two ceremonies. The first one –public and sumptuous, was followed by a much more modest ceremony of private, almost intimate character. Death is not only about mourning. While Eliza could recover from the pain of bereavement after the death of her daughter, the deaths of her father‑in‑law, Wincenty Krasiński and her husband, Zygmunt Krasiński, one of the greatest Romantic poets, forced her to start a new chapter in life. After the death of her father‑in‑law, Eliza had to take over the administration of the estate. When her husband passed away, she also had to preserve the literary heritage of the poet. Meanwhile, in the period between the funerals of Wincenty Krasiński in 1858 and her husband in 1859, Eliza began a close relationship with Ludwik Krasiński. Surrounded by scandal, she married Ludwik in 1860.